ROK 1956 W POLSCE – DYSKUSJE PRAWNIKÓW O SĄDACH, PROKURATURACH I PRAWIE KARNYM - Maksimiuk, Diana (Zeszyty Prawnicze, 2016)
The Year 1956 in Poland – Lawyers’ Discussions aboutbJustice, Public Prosecutors’ Offices and Criminal Law Summary The year 1956 was frequently described as a “breakthrough” in the postwar history of Poland and constituted the end of the Stalin’s epoch. The change of the political conditions which took place during that time, as well as accompanying freedom of speech, created unlimited opportunity to criticise that period. In deliberation of the state of Poland the debate about the issue of the justice has been also led. The law society which participated actively in those events was aimed mainly at restoring the rule of law and reconstructing the justice’s authority. Definitely, the most important matter under discussion was to deal with the past. Criticism and even self-critical opinions occured together with proposals concerning the future situation. Among so many solutions which have been presented by lawyers, the most noticeable was the tendency to bring the status of prewar law back. Although this returing was not achieved, in consequence of that debate the transformation which symbolised new age was introduced.